2019
DOI: 10.14738/abr.12.5241
|View full text |Cite
|
Sign up to set email alerts
|

Trust-Significance, Definitions and Dimensions: A Literature Search

Abstract: This is a literature based paper addressing the significance, definitions and dimensions of trust. Trust is a crucial subject matter for many social science disciplines. Researchers could reveal that trust reduces risk, increases productivity, builds a strong relationship between the colleagues in the work place, helps in transferring knowledge between the individuals and organisations, builds team work, minimizes controls, reduces expenditures, reduces competitive attitudes and makes decision making easy. Tru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 36 publications
(65 reference statements)
0
0
0
Order By: Relevance
“…Parasuraman, Valarie A. Zeithaml, 1985;Othman & Owen, 2001) has a direct and indirect relationship with trust (Boonlertvanich, 2019). From various previous studies it has been reported that service quality has a direct and positive effect on trust customers (Abror et al, 2022;Adiwijaya & Subagio, 2017;Alfiyanto, Indriani, & Perdhana, 2020;Fauzi & Suryani, 2019;Hasnain, 2019;Oliveira et al, 2017).Thus the proposed hypothesis is as follows H5: SQ has a direct effect on trust…”
Section: Sq Affects Trustmentioning
confidence: 97%
See 3 more Smart Citations
“…Parasuraman, Valarie A. Zeithaml, 1985;Othman & Owen, 2001) has a direct and indirect relationship with trust (Boonlertvanich, 2019). From various previous studies it has been reported that service quality has a direct and positive effect on trust customers (Abror et al, 2022;Adiwijaya & Subagio, 2017;Alfiyanto, Indriani, & Perdhana, 2020;Fauzi & Suryani, 2019;Hasnain, 2019;Oliveira et al, 2017).Thus the proposed hypothesis is as follows H5: SQ has a direct effect on trust…”
Section: Sq Affects Trustmentioning
confidence: 97%
“…Customer trust is defined as a form of customer thoughts, feelings, emotions, or behavior that service/product providers can rely on to act in their best interest (Abror et al, 2022;Hasnain, 2019;Li, Teng, & Chen, 2020). Meanwhile, another definition states that it is the customer's belief that banking management will not do anything that is detrimental to him as a customer (Al Qundus, Paschke, Kumar, & Gupta, 2019).…”
Section: Trustmentioning
confidence: 99%
See 2 more Smart Citations